2015
DOI: 10.1111/jam.12823
|View full text |Cite
|
Sign up to set email alerts
|

Organic neem compounds inhibit soft-rot fungal growth and improve the strength of anthracite bricks bound with collagen and lignin for use in iron foundry cupolas

Abstract: This novel organic fungicidal treatment may increase the storage and performance of anthracite bricks in iron foundries, thereby saving 15-20% of the energy used in conventional coke production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Neem ( Azadirachta indica ), an Indian medicinal herb, is now widely planted in many Asian and African countries 1 . Neem oil, derived from the seeds or fruits of the neem tree through pressing or extraction, exhibits broad spectrum of pharmacological properties, including antiparasitic, antifungal, antibacterial, antimalarial, and anti-inflammatory activities 2 3 4 5 6 7 . Our previous studies obtained a new compound from neem oil, which was identified as octadecanoic acid-3, 4-tetrahydrofuran diester 8 9 ( Fig.…”
mentioning
confidence: 99%
“…Neem ( Azadirachta indica ), an Indian medicinal herb, is now widely planted in many Asian and African countries 1 . Neem oil, derived from the seeds or fruits of the neem tree through pressing or extraction, exhibits broad spectrum of pharmacological properties, including antiparasitic, antifungal, antibacterial, antimalarial, and anti-inflammatory activities 2 3 4 5 6 7 . Our previous studies obtained a new compound from neem oil, which was identified as octadecanoic acid-3, 4-tetrahydrofuran diester 8 9 ( Fig.…”
mentioning
confidence: 99%
“…As a result, essential oils and plant secondary metabolites are the primary ingredients in biopesticide formulations . Neem or Azadirachta indica (Meliaceae family) is evidence of research in agricultural and medicinal fields. , Neem oil has a variety of bioactive compounds, the most prominent of which are triterpenes such as limonoids, and among limonoids, azadirachtin is the most important. , Neem oil is low-cost, hydrophobic, and biodegradable with diverse potent applications in the food, agriculture, and health sectors . Due to a variety of bioactive phytochemicals present in neem oil, like azadirachtin, nimbidin, salannin, margolone, gedunin, isomargolonone, nimbolide, margolonone, and others, neem oil has potent antibacterial, plasticizer, antifungal, pesticidal, insecticidal, and antioxidant properties …”
Section: Introductionmentioning
confidence: 99%
“…Neem, Azadirachta indica A. Juss, a species belonging to the Meliaceae family, has been a target of research in medicinal and agricultural elds owing to the presence of important bioactive terpenoid microcomponents. [6][7][8] There are over one hundred bioactive compounds such as azadirachtin, salannin, meliantriol, nimbin and nimbidi, desacetylnimbin, azadiradione, azadirone, nimbolin, nimbinene, and nimbolide, showing ovicidal, antifungal, antibacterial, immunostimulant and acaricidal properties; besides polysaccharides and phenolic compounds. [9][10][11] According to Pinto and Lanças (2010) 12 the predominant composition of neem oil fatty acids is of oleic acid (41.09%), stearic (20.61%), palmitic (20.18%) and linoleic (14.08%), being the unsaturated sensitive to structural chemical transformation by usual oxidative processes like the ozonolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 4 and 5 react with each other by cycloaddition to render the ozonides (6) and aldehydes. 3,8,[15][16][17] In presence of protic solvents it is obtained alkoxy hydroperoxides (7) and/or peroxy hemiacetals (8) 13 (Scheme 1) that are responsible for the therapeutic effects of ozonated oils. 18 According to Bocci (2005;2006) 19,20 the healing effect of ozonated oils is likely to arise by the formation of hydrogen peroxide and other products from lipid oxidation when the ozonides interact with wound exudate.…”
Section: Introductionmentioning
confidence: 99%